Implementasi Integrasi Keilmuan dalam Pendidikan Pesantren melalui Islamisasi Ilmu Pengetahuan - Al Mubarok, Abdullah; Maimun, Ach; Eko Riyadi, Dedi (JSP: Jurnal Studi Pesantren, 2024)
The dichotomy between religious knowledge and science has become a significant epistemological problem in contemporary Islamic education, hindering holistic development of Muslim scholars. This qualitative library research analyzes the conceptualization and implementation of knowledge integration in pesantren education through the Islamization of knowledge framework proposed by Syed Naquib al-Attas. Using content analysis method on primary literature including seminal works of al-Attas and al-Faruqi, as well as secondary literature on integration practices in pesantren, this study addresses three main questions: how is the concept of knowledge integration constructed, how is it implemented in curriculum and teaching methods, and what are its theoretical and practical implications. The findings reveal that knowledge integration is operationalized through two principles: separating Western concepts contradictory to Islamic values and incorporating key Islamic concepts into modern sciences. Implementation is carried out through ta'dib as educational objective and balanced curriculum integrating religious sciences (fardhu 'ain) with rational sciences (fardhu kifayah). The implications include increased collaboration between religious and scientific knowledge, development of multidisciplinary curriculum producing accomplished students, and transformation of educators' roles into knowledge connectors. This research contributes to the discourse on Islamization of knowledge in contemporary pesantren context and provides frameworks for designing effective knowledge integration programs.